The use of co-design with young people for digital mental health support development: A systematic review - Órla McGovern; Shauna Glennon; Isobel Walsh; Pamela Gallagher; Darragh McCashin (Internet Interventions)
Co-design methods offer an opportunity to meaningfully involve young people in research to ensure that designed supports are useable and responsive to their needs. However, how co-design is currently being applied with young people in the digital mental health field is unclear. This review aimed to critically synthesise the use of co-design with young people to design or modify digital mental health interventions and supports. Six databases were searched for empirical papers published in English from 2012 onwards. Papers were included if they reported on young people aged up to 25 years of age who were involved in the co-design of an online mental health intervention or support. A narrative synthesis of 30 papers meeting these specific criteria was completed. The results highlighted an interchangeable and inconsistent terminology used to described co-design and related approaches across papers. The level of inclusion of young people varied and there was a lack of consideration for power dynamics. Future research should aim to establish a clear and consistent definition and terminology for co-design along with a rigorous gold-standard framework for reporting co-design in order to ensure the process is being carried out in line with its original purpose. Implications for research and practice in the youth co-design field are discussed.